PROFIL PENGELOLAAN EMERGENCY TROLLEY DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT UMUM DAERAH Dr.M.YUNUS BENGKULU - Febrianti Sihotang (Jurnal Vokasi Keperawatan (JVK), 2020)
Emergency trolley is a trolley that contains equipment and medicines for emergencies, where there is a sudden and unexpected deterioration in the clinical condition of the patient which can immediately cause death or cause long-term health so that immediate intervention or resuscitation is needed. Good management of emergency trolley can improve the quality of health services in the environment of Dr. M.Yunus Bengkulu Hospital, especially emergency services. The research has been conducted on the management of emergency trolley in the Emergency Room of Dr. M.Yunus Bengkulu Hospital. Emergency trolley at Dr. M.Yunus Bengkulu Hospital guides and applies emergency trolley management standards according to procedures so that the quantity and quality of storage and completeness are maintained. The purpose of this research is to determine the readiness and availability of emergency trolley management standards, especially in the Emergency Room Installation  Dr. M.Yunus Bengkulu Hospital. This research is descriptive in nature with a qualitative approach, primary data collection through direct observation, comprising of observing human resources, facilities and infrastructure as well as the process of managing an emergency trolley at RSUD Dr. M.Yunus Bengkulu Hospital. Secondary data collection is conducted through tracing guidelines or procedures for managing emergency trolley used, as well as documents related to management of emergency trolley at RSUD Dr. M.Yunus Bengkulu Hospital. The results of the study are compiled and presented in the form of a checklist table of observations and in the form of a narrative about human resources, facilities and infrastructure as well as the process of managing an emergency trolley at Dr. M.Yunus Bengkulu  Hospital.